Unwanted effects of X-rays in surface grafted copper(ii) organometallics and copper exchanged zeolites, how they manifest, and what can be done about them. Issue 13 (18th March 2020) - Newton, Mark A.; Knorpp, Amy J.; Meyet, Jordan; Stoian, Dragos; Nachtegaal, Maarten; Clark, Adam H.; Safonova, Olga V.; Emerich, Hermann; van Beek, Wouter; Sushkevich, Vitaly L.; van Bokhoven, Jeroen A.
Abstract : Commonly applied powder densities at modern X-ray spectroscopy resources have the capacity to affect, in a deleterious manner, the results obtained from a measurement on copper(ii ) containing materials. Abstract : Copper(ii ) containing materials are widely studied for a very diverse array of applications from biology, through catalysis, to many other materials chemistry based applications. We show that, for grafted copper compounds at the surface of silica, and for the study of the selective conversion of methane to methanol using copper ion-exchanged zeolites, the application of focused X-ray beams for spectroscopic investigations is subject to significant challenges. We demonstrate how unwanted effects due to the X-rays manifest, which can prevent the study of certain types of reactive systems, and/or lead to the derivation of results that are not at all representative of the behavior of the materials in question. With reference to identical studies conducted at a beamline that does not focus its X-rays, we then delineate how the total photon throughput and the brilliance of the applied X-rays affect the apparent behavior of copper in zeolites during the stepwise, high temperature and aerobic activation approach to the selective conversion of methane to methanol. We show that the use of increasingly brilliant X-ray sources for X-ray spectroscopy can bring with it significant caveats to obtaining valid and quantitative structure–reactivity relationships (QSARS) and kinetics for this class of material. Lastly, through a systematic study of these effects, we suggest ways to ensure that valuable allocations of X-ray beam time result in measurements that reflect the real nature of the chemistry under study and not that due to other, extraneous, factors.